Fatigue prevalence and associated factors in patients with multiple system atrophy. (16th June 2021) - Xu, Fang; Wang, Hui; Zhao, Quanzhen; Huang, Hongyan; Ning, Pingping; Shen, Qiuyan; Xie, Dan; Lu, Haitao; Xu, Yanming
Abstract: Objective: Fatigue was reported a determinant of poor quality of life in multiple system atrophy (MSA) patients. This study aimed to determine fatigue prevalence and associated demographic, motor, and non‐motor symptoms in MSA patients. Materials and methods: A total of 174 MSA patients met "Probable" diagnostic criteria were included in this cross‐sectional study. Fatigue Severity Scale (FSS) was used to measure fatigue prevalence. Unified MSA Rating Scale (UMSARS), Non‐Motor Symptoms Scale (NMSS), Hamilton Depression Rating Scale‐17 (HDRS‐17), Hamilton Anxiety Scale (HAMA), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), REM Sleep Behavior Disorder Screening Questionnaire (RBDSQ), and Mini‐Mental State Exam (MMSE) were used for comprehensive clinical assessments. Nonparametric Mann–Whitney or Pearson's chi‐square test was used to compare the patient score with or without fatigue (defined as a mean FSS score≥4). Binary logistic regression analysis was performed to determine features independently associated with the presence of fatigue. Results: Fifty (28.7%) patients enrolled reported fatigue. Results of multivariate analysis revealed that anxiety (OR = 3.01, 95% CI = 1.43–6.31), excessive daytime sleepiness (OR = 2.70, 95% CI = 1.23–5.90), and use of sleep medicine (OR = 3.58, 95% CI = 1.39–9.24) were significantly associated with fatigue in MSA patients. Conclusions: Fatigue is common in our MSA patients. Anxiety, excessive daytime sleepiness, and current sleep medicine use may be associated with an increased risk of fatigue. However, the severity of motor symptoms may not be associated with fatigue. Our findings highlight the need to identify, investigate, and treat fatigue in MSA.